Usulan Perancangan Tata Letak Gudang dengan Menggunakan Metode Class Based Storage - Aryansah, Nicky Fenky; Murnawan , Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
CV.  Bandung Central Arteri Samudra is a manufacturing industry engaged in the distribution of fishing equipment located on Jalan Kembang Jepun no.  194 – 196, ex.  Nyamplungan subdistrict of Pabean Cantikan Surabaya.  This research examines the warehouse layout using the "class based storage" method in warehouses at CV.  Bandung Central Arteri Samudra.  This method aims to increase the efficiency of storing and retrieving goods in the warehouse by grouping goods based on certain classes or characteristics.  This study involves data analysis, layout planning, and implementation of "class based storage" methods in the company's warehouse operations.  The research results show that this method can optimize the use of warehouse space and reduce the time required to access goods.  Additionally, improvements in productivity and operational efficiency were also seen.  The practical implication of this research is that the use of the "class based storage" method can provide significant benefits in warehouse management at CV.  Bandung Central Arteri Samudra